A gadolinium(iii) complex based dual-modal probe for MRI and fluorescence sensing of fluoride ions in aqueous medium and in vivo. Issue 44 (30th August 2016) - Wang, Yue; Song, Renfeng; Guo, Ke; Meng, Qingtao; Zhang, Run; Kong, Xiangfeng; Zhang, Zhiqiang
Abstract : A novel Gd(iii ) complex based dual-modal probe, Gd(TTA)3 -DPPZ was designed and assembled for the simultaneous fluoride ion in aqueous media and in vivo . Abstract : A novel Gd(iii ) complex, Gd(TTA)3 -DPPZ, was designed and assembled as a dual-modal probe for the simultaneous fluorescence and magnetic resonance imaging (MRI) detection of fluoride ions in aqueous media and in vivo . In this system, the Gd(iii ) center is not only serving as a MRI signal output unit, but also as a binding site for fluoride ions. When appropriate equivalents of fluoride ions were added into the solution of Gd(TTA)3 -DPPZ, the replacement of the coordination water led to a decrease of the longitudinal relaxivity ( r 1 ) as well as distinct spectroscopic changes, by which MRI/fluorescence dual-modal fluoride ion sensing was achieved. In the presence of fluoride ions, a 2-fold fluorescence emission enhancement of Gd(TTA)3 -DPPZ, and a notable decrease of the UV–vis absorption spectrum were observed. The fluorescence detection limit for fluoride ions was established at 70 nM. Gd(TTA)3 -DPPZ also exhibits about 75% decrease of the longitudinal relaxivity ( r 1 ) upon addition of fluoride ions in aqueous medium. The appropriate blood circulation time of Gd(TTA)3 -DPPZ allows its potential application in MRI in vivo . The results demonstrated that Gd(TTA)3 -DPPZ could serve as a potential MRI/fluorescence bimodal imaging agent for the specific and high-sensitive sensing of fluoride ions in vivo .